MicroRNA-155 Exerts Cell-Specific Antiangiogenic but Proarteriogenic Effects During Adaptive Neovascularization. Issue 18 (5th May 2015) - Pankratz, Franziska; Bemtgen, Xavier; Zeiser, Robert; Leonhardt, Franziska; Kreuzaler, Sheena; Hilgendorf, Ingo; Smolka, Christian; Helbing, Thomas; Hoefer, Imo; Esser, Jennifer S.; Kustermann, Max; Moser, Martin; et al.
<x xml:space="preserve">Abstract</x> Background— Adaptive neovascularization after arterial occlusion is an important compensatory mechanism in cardiovascular disease and includes both the remodeling of pre-existing vessels to collateral arteries (arteriogenesis) and angiogenic capillary growth. We now aimed to identify regulatory microRNAs involved in the modulation of neovascularization after femoral artery occlusion in mice. Methods and Results— Using microRNA-transcriptome analysis, we identified miR-155 as a downregulated microRNA during hindlimb ischemia. Correspondingly, inhibition of miR-155 in endothelial cells had a stimulatory effect on proliferation and angiogenic tube formation via derepression of its direct target gene angiotensin II type 1 receptor. Surprisingly, miR-155–deficient mice showed an unexpected phenotype in vivo, with a strong reduction of blood flow recovery after femoral artery ligation (arteriogenesis) dependent on the attenuation of leukocyte-endothelial interaction and a reduction of proarteriogenic cytokine expression. Consistently, miR-155–deficient macrophages exhibit a specific alteration of the proarteriogenic cytokine expression profile, which is partly mediated by the direct miR-155 target gene SOCS-1. Conclusions— Our data demonstrate that miR-155 exerts an antiangiogenic but proarteriogenic function in the regulation of neovascularization via the suppression of divergent cell-specific target genes and that its expression in both endothelial and bone marrow–derived cells is essential for arteriogenesis in response to hindlimb ischemia in mice.